Analysis of Chatime Customer Loyalty through Customer Experience and Perceived Quality with Brand Reputation as Intervening Variable - Wibowo, Bagus Yunianto (Politeknik Negeri Semarang, 2021)
This research was conducted to determine consumer loyalty or customer loyalty of chatime outlets through customer experience and perceived quality with brand reputation as an intervening variable during the Covid-19 pandemic. Respondents in this study were visitors to chatime outlets from students and workers in Semarang city with a sample of 100 respondents from the entire population. This study uses confirmatory factor analysis techniques and maximum likelihood estimation on SEM (Structural Equations Modeling) from the statistical package AMOS 24.0 (Analysis of Moment Structure). The data collection technique used a questionnaire with a Likert scale. The parameter estimation results are in accordance with the hypothesis that customer experience significantly affects brand reputation with a critical ratio (cr) of 5.100 and P-Value ***, perceived quality has a positive effect on brand reputation with a critical ratio (cr) of 6.637 and P-Value ***, and brand reputation has a positive effect on customer loyalty with a critical ratio (cr) of 9,231 and P-Value ***. From this study it can be learned that in the midst of the Covid-19 pandemic, consumers are still very enthusiastic and loyal to buy chatime both online or come to chatime outlet even though there are many similar competitors with lower prices